Economic Growth and Equality of Opportunity - Peragine, Vito; Palmisano, Flaviana; Brunori, Paolo (World Bank, Washington, DC, 2013)
The paper proposes an approach to understand the relationship between inequality and economic growth obtained by shifting the analysis from the space of final achievements to the space of opportunities. To this end, it introduces a formal framework based on the concept of the Opportunity Growth Incidence Curve. This framework can be used to evaluate the income dynamics of specific groups of the population and to infer the role of growth in the evolution of inequality of opportunity over time. The paper shows the relevance of the introduced framework by providing two empirical analyses, one for Italy and the other for Brazil. These analyses show the distributional impact of the recent growth experienced by Brazil and the recent crisis suffered by Italy from both the income inequality and opportunity inequality perspectives.